With Grief and Joy — Crip Pandemic Life: A Tapestry, Part II - Theodora Danylevich; Alyson Patsavas (Lateral, 2023)
This second installment of “Crip Pandemic Life: A Tapestry” opens with a reflection on transformative access and its visioning work. We weave this discussion through not only the eight new pieces found within this issue, but also through a reflection on the practices of access and care that enabled the writing, editing, and publication process itself. We conclude with two artifacts: The first is the “Accessible Knowledge Production Manifesto” that emerged as a collectively authored set of demands generated at a workshop we held in connection to the launch of our first installment of “Crip Pandemic Life.” The second is a link to a resource list, “Continuing Threads and Proliferations; Crip Pandemic Life Archive,” compiled by Corbin Outlaw, which links out to other pandemic projects documenting crip, disabled, chronically-ill, mad, and neurodivergent experiences, particularly highlighting experiences not captured within our tapestry of crip pandemic life.